2008
DOI: 10.1897/07-096.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of estrogenicity of sewage effluent and reclaimed water using vitellogenin as a biomarker

Abstract: To evaluate the quality of reclaimed water, the estrogenicity of effluent from a sewage treatment plant and of reclaimed water treated with coagulation-sedimentation-filtration using the effluent as raw water was assessed using vitellogenin (VTG) as a biomarker. After a three-week exposure, significant (p < 0.05) induction of VTG occurred in female crucian carp (Carassius carassius) exposed continuously to the secondary effluent and reclaimed water with different dilutions (12.5, 25, 50, and 100% for secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…In contrast to our results, a study with crucian carp showed that VTG levels in immature female and male carps were reduced when the wastewater was treated with ozone [ 20 ]; however, the carps already had higher VTG induction in the normal effluent compared with controls and our trout did not show higher VTG levels in the normal effluent compared with the negative controls.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to our results, a study with crucian carp showed that VTG levels in immature female and male carps were reduced when the wastewater was treated with ozone [ 20 ]; however, the carps already had higher VTG induction in the normal effluent compared with controls and our trout did not show higher VTG levels in the normal effluent compared with the negative controls.…”
Section: Resultscontrasting
confidence: 99%
“…However, there are conflicting findings on the residual toxicity as well as biological effects of ozonated wastewater. Some studies observed reduced toxicity of ozonated wastewater, for example, in terms of reduced estrogenicity in fish (An et al, 2008;Filby et al, 2010;Gunnarsson et al, 2009), and reduced genotoxic activity of bacteria, plant, and mammalian cells (Mišík et al, 2011). Other studies reported potentially adverse effects on exposed biota, for example increased reproduction of water flea Ceriodaphnia dubia (Blatchley et al, 1997), increased cytochrome P450 (CYP) induction in nematode Caenorhabditis elegans (Abbas et al, 2018), and increased reproduction and estrogenicity as well as decreased activity in fish (Pohl et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As endpoints, biochemical biomarkers of sub-lethal effects such as the enzymes catalase (CAT), cholinesterase (ChE), and cytochrome P450 (CYP), have been measured in various aquatic species to establish their ability to reflect pollution in the aquatic environment (Sarkar et al, 2006;Wigh et al, 2017;Rodrigues et al, 2019). To evaluate the residual toxicity of wastewater treated with ozonation and other additional wastewater treatment techniques, vitellogenin (VTG) has been used as a biomarker for estrogenicity in fish (An et al, 2008;Gunnarsson et al, 2009;Filby et al, 2010). A new group of potential biochemical biomarkers are oxylipins (the oxylipidome).…”
Section: Introductionmentioning
confidence: 99%